Trump’s Muslim immigration ban: ideology political opportunism? - Saidani, Rima; Afkir ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2019)
This research examines the nature of Trump’s anti-Muslim rhetoric which was delivered during the 2016 U.S. presidential elections. It also discusses his policy on Muslim immigrants and its implications. The purpose of this work is to investigate the motives behind Trump’s discourse of hatred against Muslims. It also seeks to analyze the contradictions and the outcomes of Trump’s policy on Muslim immigrants. In order to reach this purpose, the research relied on the observation of the republican candidate’s speeches, declarations, and political experts’ analysis and interviews that were conducted with them. It seems that Trump’s anti-Muslim rhetoric was a fusion of ideology and political opportunism. On the one hand, Trump was convinced that a large segment of Muslims hate the U.S. Thus, the American government should take a restrictive stance on Muslim immigration. In addition, he advanced the protection of the national security in order not to bear the heavy burden of refugees coming from the “terror-prone places”. On the other hand, Trump used an anti-Muslim rhetoric as a political tool that might have strengthened his chances in winning the 2016 U.S. presidential elections. In order to fulfill his campaign promise, the forty-fifth American president issued one of the most controversial executive orders on Muslim immigrants. His travel ban gave no mention to some Muslim countries despite having troublesome terrorist issues. This exclusion contradicts Trump’s campaign. The republican president’s real motives are a combination of pragmatism and ideology. Although Trump strongly believes in something, he implements policies which may be a bit different from his conviction because of trade interest